DETERMINANT AFFECTING THE AUDIT DELAY WITH COMPANY SIZE AS VARIABLE MODERATING (CASE STUDY OF MINING COMPANIES REGISTERED ON BEI) - Rohaelis Nuraisiah , Anggi haerani , Rika Kartika, S.T., M.Ak , Lona noviani , Sukarta Atmaja.S. Sos.,MM , Mukhtar Eri Suhaeri (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This study aims to determine the effect of profitability, audit opinion and audit of audit delay, and to determine the size of acceptance audit delay, auditor audits of audit delay, and solvency of audit delay. This study uses data analysis techniques Moderated Regression Analysis with 22 samples in the mining sector companies listed on the Indonesia Stock Exchange with observation period 2012-2016 so the total observation to 110 samples. The results showed that profitability did not significantly affect the audit delay, Audit Opinion did not significantly affect the audit delay, while solvency had a significant positive effect on audit delay. Firm size is able to moderate (strengthen) the effect of solvency on audit delay. But able to moderate (weaken) the effect of profitability on audit delay and not able to moderate the influence of audit opinion with audit delay